A mycotoxin detoxification agent, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611293864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
然而,游离枯草芽孢杆菌的短板十分突出:在饲料制粒过程中70~90℃的高温环境以及畜禽胃酸pH 2.5~4.0的条件下,芽孢大量失活;菌体分散于饲料中,与霉菌毒素的接触概率较低,在高毒素污染的日粮中脱毒效率不足
本发明通过钠化改性提升蒙脱石的阳离子交换容量,再借助溶剂剥层工艺扩大蒙脱石的比接触面积,促使经氯化锌改性的粮油加工废弃物与剥层蒙脱石充分紧密接触;随后在惰性环境中进行高温煅烧,制备得到高比表面积的碳基蒙脱石复合材料。进一步利用碳基蒙脱石复合材料表面有机官能团的吸附作用,将枯草芽孢杆菌固载于碳基蒙脱石复合材料表面。
Smart Images

Figure CN122974281A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical fields of resource utilization of grain and oil processing waste, clay mineral modification, microbial immobilization and feed safety additives, specifically including a mycotoxin detoxifier and its preparation method and application. Background Technology
[0002] Feed ingredients such as corn, soybean meal, and wheat bran are highly susceptible to contamination by Fusarium and Aspergillus during planting, storage, and processing, leading to the production of three highly hazardous mycotoxins: aflatoxin B1 (AFB1), vomitoxin (DON), and zearalenone (ZEN). When livestock and poultry consume moldy feed, these mycotoxins can damage the intestinal barrier, inhibit the body's antioxidant capacity, and harm the liver, kidneys, and reproductive organs, resulting in stunted growth, reproductive disorders, and weakened immunity. Furthermore, these toxins can accumulate in human bodies through meat, eggs, and dairy products, posing a significant food safety hazard. Currently, the mainstream detoxification methods in the feed industry mainly include two categories: inorganic mineral adsorbents and probiotic biodetoxifiers. However, both have significant drawbacks when used alone.
[0003] Montmorillonite is a layered aluminosilicate clay mineral that exhibits excellent adsorption of polar AFB1 due to its interlayer cation exchange capacity. However, its single interlayer pore structure and poor hydrophobicity result in low adsorption capacity for lipid-soluble DON and ZEN. Furthermore, the adsorption process is reversible in the neutral environment of livestock gastric juice and intestines, leading to easy desorption of toxins. Grain-based carbon materials are products of anaerobic pyrolysis of grain and oil processing waste. They have some adsorption capacity for lipid-soluble mycotoxins, but their ion exchange capacity is weak, resulting in poor AFB1 removal. Additionally, the powder is prone to agglomeration, has low mechanical strength, and suffers significant processing losses when added alone. Currently, materials prepared by simply combining grain-based carbon materials with montmorillonite only achieve a simple superposition of the properties of the two raw materials. The interfacial bonding is loose, and the pore structure cannot be precisely synergistically controlled, failing to achieve a broad-spectrum and stable detoxification effect. Moreover, relying solely on physical adsorption cannot completely eliminate toxin toxicity.
[0004] Bacillus subtilis is a nationally approved probiotic for feed, possessing a dual detoxification function: firstly, its cell wall contains peptidoglycan, lipoteichoic acid, and glucan, which physically adsorb mycotoxins through electrostatic and hydrophobic interactions; secondly, its metabolically secreted epoxidase, laccase, and esterase can cleave the epoxy groups of DON, the lactone ring of ZEN, and the furan ring of AFB1, eliminating toxin toxicity at the molecular level. Furthermore, this bacterium can colonize the intestines, alleviating intestinal oxidative damage caused by mycotoxins. However, free Bacillus subtilis has significant drawbacks: during feed pelleting at high temperatures of 70–90°C and under the acidic conditions of livestock stomachs (pH 2.5–4.0), a large number of spores are inactivated; the bacterial cells are dispersed in the feed, resulting in a low probability of contact with mycotoxins, leading to insufficient detoxification efficiency in highly contaminated diets.
[0005] Existing technologies involve directly and physically mixing montmorillonite with Bacillus subtilis. However, due to the lack of a supporting structure, the montmorillonite sheets can damage the spores during extrusion, preventing the carrier from effectively enriching toxins. The adsorption and degradation pathways are disconnected, resulting in weak synergistic effects. Traditional carrier modification often employs high-temperature activation with strong acids and alkalis, generating large amounts of wastewater and incurring high production costs, making it difficult to scale up for feed production.
[0006] In summary, how to achieve broad-spectrum, long-lasting, and low-nutrient-loss mycotoxin detoxification, and how to construct an integrated adsorption-degradation composite detoxification material, remains a challenge for current research. Summary of the Invention
[0007] In view of the above-mentioned defects in the prior art, the first objective of the present invention is to provide a method for preparing a mycotoxin detoxifier.
[0008] A second objective of this invention is to provide a mycotoxin detoxifier.
[0009] The third objective of this invention is to provide an application of a mycotoxin detoxifier in the removal of mycotoxins.
[0010] To achieve the first objective mentioned above, the technical solution adopted by the present invention includes: This invention discloses a method for preparing a mycotoxin detoxifier, comprising the following steps: S1. Calcium-based montmorillonite is converted into sodium-based montmorillonite by sodium conversion, and then exfoliated montmorillonite is obtained after swelling and exfoliation treatment. S2. The crushed grain and oil processing waste is immersed in zinc chloride solution and then thermally activated to obtain activated grain and oil processing waste. S3. Mix the exfoliated montmorillonite with activated grain and oil processing waste evenly, dry it, and calcine it under an inert atmosphere to obtain a carbon-based montmorillonite composite material. S4. The obtained carbon-based montmorillonite composite material is thoroughly mixed with Bacillus subtilis bacterial solution and centrifuged to obtain carbon-based montmorillonite composite material loaded with Bacillus subtilis.
[0011] Furthermore, the grain and oil processing waste is derived from one or more of the following: straw, peanut shells, rapeseed shells, sunflower seed shells, cottonseed shells, corn cobs, and tea seed shells.
[0012] This invention modifies the structure of conventional calcium-based montmorillonite through sodium modification, optimizing its interlayer structure and surface physicochemical properties. This significantly improves ion exchange performance, interlayer expansion capacity, and system dispersion stability, providing excellent structural carriers and reaction conditions for subsequent carbon material composites and functional microbial immobilization. Using grain and oil processing byproducts as a low-cost biomass carbon precursor, this invention mixes them with exfoliated montmorillonite and then calcines them at high temperatures, enabling the in-situ construction of stable carbonaceous porous structures in the montmorillonite surface and interlayer pores.
[0013] This carbon-based montmorillonite composite material not only effectively enhances the structural strength, physicochemical stability, and anti-interference ability of the montmorillonite matrix, significantly improving the material's adsorption and capture performance for mycotoxins, but also constructs a microenvironment suitable for microbial growth and attachment, effectively shielding against the adverse effects of complex external matrices and ensuring the biological activity of Bacillus subtilis. Furthermore, the surface of the carbon-based montmorillonite composite material is rich in various active functional groups, which can achieve orderly and tight loading of Bacillus subtilis on the material surface through multiple mechanisms such as electrostatic interaction, hydrogen bonding, and functional group coordination. This improves upon the defects of traditional physical adsorption, such as uneven adhesion, weak binding force, and easy detachment of bacteria, effectively enhancing the overall stability and application reliability of the composite functional system.
[0014] The loading process of functional strains is the core technology of this invention, which breaks through the limitations of traditional single adsorbent materials and constructs an integrated adsorption-biodegradation functional system. This invention uses a mild physical composite method to combine microorganisms with the functional carrier, eliminating the need for harsh preparation conditions such as strong acids and alkalis or high-temperature cross-linking. This maximizes the preservation of the cellular structure integrity and bio-metabolic activity of Bacillus subtilis, ensuring that the strain can continuously exert its toxin degradation effect in complex real-world systems such as feed and grain / oil products. This mycotoxin detoxifier fully combines the excellent adsorption and enrichment performance of carbon-based montmorillonite composite materials with the efficient biodegradation advantages of Bacillus subtilis, forming a synergistic mechanism of material adsorption and microbial degradation. It can effectively overcome the challenges of treating weakly polar and difficult-to-remove mycotoxins such as vomitoxin. Compared to traditional single adsorbent materials, this mycotoxin detoxifier can achieve both enrichment adsorption and complete degradation of pollutants, possessing outstanding advantages such as high detoxification efficiency, thorough treatment effect, and good long-term stability. It provides a novel and practical technical solution for the green treatment and efficient control of mycotoxin pollution in the grain, oil, and feed industries.
[0015] Furthermore, the mass ratio of the exfoliated montmorillonite to the activated grain and oil processing waste is 1:1-20; for example, the mass ratio of the exfoliated montmorillonite to the activated grain and oil processing waste can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, etc.
[0016] Furthermore, the swelling and exfoliation treatment further includes adding formamide solution to sodium montmorillonite under an inert atmosphere and reacting for a period of time to obtain exfoliated montmorillonite.
[0017] Furthermore, the mass-to-volume ratio of the sodium-based montmorillonite and the formamide solution is 0.8-1.2 g: 50 mL.
[0018] Furthermore, the reaction temperature of sodium montmorillonite and formamide solution is 40-60℃, and the reaction time is 12-36h.
[0019] Furthermore, the Bacillus subtilis is Bacillus subtilis ags617, which was deposited at the China General Microbiological Culture Collection Center on March 6, 2026, with accession number CGMCC No. 37860.
[0020] Furthermore, the viable count of the Bacillus subtilis bacterial solution is 5 × 10⁻⁶. 8 -1×10 9 CFU / mL.
[0021] Furthermore, the mass-to-volume ratio of the grain and oil processing waste to the zinc chloride solution is 1 g: 3-5 mL. The mass fraction of the zinc chloride solution can be 55%.
[0022] Furthermore, in step S2, the thermal activation temperature is 40-60℃ and the thermal activation time is 8-15h.
[0023] Furthermore, the time for mixing the exfoliated montmorillonite with the activated grain and oil processing waste is 0.5-3 h.
[0024] Furthermore, in step S3, the calcination temperature is 400-450℃, preferably 400℃, and the calcination time is 0.5-3 h, preferably 1 h.
[0025] Furthermore, the mass-to-volume ratio of the carbon-based montmorillonite composite material and the Bacillus subtilis bacterial solution is 1 mg: 1-5 mL.
[0026] Furthermore, in step 4), in order to ensure that Bacillus subtilis is loaded into the pores of the carbon-based montmorillonite composite material, the mixing and stirring time should be extended to 4-6 hours.
[0027] To achieve the second objective mentioned above, the technical solution adopted by the present invention includes: This invention discloses a mycotoxin detoxifier prepared by the preparation method described above.
[0028] To achieve the third objective mentioned above, the technical solution adopted by the present invention includes: This invention discloses the application of the mycotoxin detoxifier described above in the removal of mycotoxins.
[0029] Furthermore, the application further includes: The mycotoxin detoxifier was added to the mycotoxin solution and adsorbed at a constant temperature under light-protected conditions.
[0030] Furthermore, the concentration of the mycotoxin solution is 1-50 mg / L; exemplaryly, the concentration range of the mycotoxin solution can also be 1-3 mg / L, 1-5 mg / L, 1-7 mg / L, 1-10 mg / L, 2-5 mg / L, 2-7 mg / L, 2-10 mg / L, 5-7 mg / L, 5-10 mg / L, 7-10 mg / L, 5-50 mg / L, 10-50 mg / L, 20-50 mg / L, 30-50 mg / L, 40-50 mg / L, 10-20 mg / L, 10-30 mg / L, 10-40 mg / L, 20-40 mg / L, 30-40 mg / L, etc.
[0031] Furthermore, the mass concentration of the mycotoxin detoxifier in the mycotoxin solution is 1-5 wt‰; exemplaryly, this mass concentration can also form any range between 1 wt‰, 1.25 wt‰, 1.5 wt‰, 1.75 wt‰, 2 wt‰, 2.25 wt‰, 2.5 wt‰, 2.75 wt‰, 3 wt‰, 3.25 wt‰, 3.5 wt‰, 3.75 wt‰, 4 wt‰, 4.25 wt‰, 4.5 wt‰, 4.75 wt‰, and 5 wt‰.
[0032] Furthermore, the isothermal adsorption conditions are isothermal adsorption at 37-45℃ for 1-3 hours.
[0033] Furthermore, the mycotoxin solution includes one or more of vomitoxin, zearalenone, fumonisin, and aflatoxin, preferably vomitoxin or zearalenone.
[0034] Beneficial effects of this invention: This invention enhances the cation exchange capacity of montmorillonite through sodium modification, and then expands the specific contact area of montmorillonite using a solvent exfoliation process, promoting thorough and close contact between zinc chloride-modified grain and oil processing waste and the exfoliated montmorillonite. Subsequently, high-temperature calcination in an inert environment yields a carbon-based montmorillonite composite material with a high specific surface area. Furthermore, the adsorption effect of the organic functional groups on the surface of the carbon-based montmorillonite composite material is utilized to immobilize Bacillus subtilis on its surface.
[0035] This invention employs a physical adsorption method to composite Bacillus subtilis with a carbon-based montmorillonite composite material, avoiding the stringent chemical cross-linking and encapsulation methods required for preparation. This approach maximizes the preservation of the cellular structure and biological activity of Bacillus subtilis, ensuring the strain's sustained and stable metabolic efficiency in the mycotoxin removal system. The synergistic effect between Bacillus subtilis and the carbon-based montmorillonite composite material results in a composite material with significantly higher adsorption and removal efficiency than conventional adsorption materials for recalcitrant, weakly polar mycotoxins such as vomitoxin. Furthermore, both the thoroughness of detoxification and the duration of action are significantly improved. Attached Figure Description
[0036] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0037] Figure 1 The image shows an XRD comparison of DC-MMT / Bacillus subtilis-400-1 prepared in Example 1 and calcium-based montmorillonite.
[0038] Figure 2 The images show SEM images of the carbon-based montmorillonite composite material prepared in Example 1 and DC-MMT / Bacillus subtilis-400-1. Figure 2 In the image, a represents a carbon-based montmorillonite composite material, b and c represent DC-MMT / Bacillus subtilis-400-1, and c is a magnified view of a portion of b. Detailed Implementation
[0039] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. It should be understood that the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0040] It should be noted that the needle filter used in this invention has no adsorption effect on mycotoxins.
[0041] The Bacillus subtilis used in the examples and comparative examples was Bacillus subtilis ags617, which was deposited at the China General Microbiological Culture Collection Center on March 6, 2026, with accession number CGMCC No. 37860.
[0042] Example 1 This example provides a method for preparing Bacillus subtilis loaded onto a carbon-based montmorillonite composite material, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) Exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material, denoted as DC-MMT, with a specific surface area of 680.9 m². 2 / g; 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier, denoted as DC-MMT / Bacillus subtilis-400-1.
[0043] Figure 1 The image shows an XRD comparison of DC-MMT / Bacillus subtilis-400-1 prepared in Example 1 with calcium-based montmorillonite, confirming that carbon has been successfully inserted into the interlayer.
[0044] Figure 2 SEM images of the carbon-based montmorillonite composite material (a) and DC-MMT / Bacillus subtilis-400-1 (b) prepared in Example 1 are shown. The carbon-based montmorillonite composite nanosheets have smooth surfaces, and after reaction with Bacillus subtilis, it was confirmed that Bacillus subtilis was attached to the surface of the nanosheets. Further magnification... Figure 2 As can be seen from Figure c, more Bacillus subtilis is loaded within the pores of the carbon-based montmorillonite composite material.
[0045] Adsorption performance The mycotoxin adsorption experiment was conducted in an aqueous solution system using a needle filter that has no adsorption effect on mycotoxins. The specific operating steps are as follows: 5 mg of DC-MMT / Bacillus subtilis-400-1 sample was accurately weighed and added to 5 mL of mycotoxin solution (10 mg / L vomitoxin solution or 10 mg / L zearalenone solution); the adsorption reaction was carried out under constant temperature of 37℃ with magnetic stirring for 3 hours. After the adsorption reaction was completed, 1 mL of the reaction solution was transferred using a syringe and filtered through a needle filter into a liquid chromatography vial; the residual content of vomitoxin or zearalenone in the filtrate was determined according to the detection method specified in the relevant national standard for feed hygiene, GB / T 30956-2014, and the adsorption rate of the material for mycotoxins was calculated accordingly. The experimental results are shown in Table 1.
[0046] Example 2 This example provides a method for preparing Bacillus subtilis loaded onto a carbon-based montmorillonite composite material, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take peanut shells, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of peanut shell fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated peanut shell fine powder. 4) Exfoliated montmorillonite and activated peanut shell powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material, denoted as HC-MMT, with a specific surface area of 713.2 m². 2 / g; 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier, denoted as HC-MMT / Bacillus subtilis-400-2.
[0047] The adsorption performance was studied in the same manner as in Example 1, and the results are shown in Table 1.
[0048] Comparative Example 1 This example provides a method for preparing modified montmorillonite without Bacillus subtilis loading, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material, denoted as DC-MMT.
[0049] The adsorption performance was studied in the same manner as in Example 1, and the results are shown in Table 1.
[0050] Comparative Example 2 This example provides a method for preparing deactivated Bacillus subtilis supported on a carbon-based montmorillonite composite material, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier. 6) Place DC-MMT / Bacillus subtilis-400-1 at 120℃ for 1 h to inactivate Bacillus subtilis.
[0051] The adsorption performance was studied in the same manner as in Example 1, and the results are shown in Table 1.
[0052] Comparative Example 3 This example provides a method for preparing carbon-based montmorillonite composite material loaded with Bacillus subtilis-modified montmorillonite, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 300 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0053] The adsorption performance was studied in the same manner as in Example 1, and the results are shown in Table 1.
[0054] Comparative Example 4 This example provides a method for preparing carbon-based montmorillonite composite material loaded with Bacillus subtilis-modified montmorillonite, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 500 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0055] The adsorption performance was studied in the same manner as in Example 1, and the results are shown in Table 1.
[0056] Comparative Example 5 This example provides a method for preparing carbon-based montmorillonite composite material loaded with Bacillus subtilis-modified montmorillonite, comprising the following steps: 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, pass through a 325-mesh standard sieve, collect the fine powder under the sieve, and obtain rice husk and straw fine powder. 4) Exfoliated montmorillonite and rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400℃ for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material, denoted as DC-MMT, with a specific surface area of 4.27 m². 2 / g; 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0057] Comparative Example 6 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) The exfoliated montmorillonite and cocamidopropyl betaine were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. Cocamidopropyl betaine can also produce pores after calcination. 4) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0058] Comparative Example 7 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 1:3 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis (cfu / mL) was stirred in a water bath at 37 °C for 1 h, centrifuged, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e., a mycotoxin detoxifier. Due to the short stirring time in step 5), Bacillus subtilis was mostly loaded on the surface of the carbon-based montmorillonite composite material rather than inside the pores.
[0059] Comparative Example 8 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Take rice husks and straw, wash them thoroughly with deionized water to remove surface dust, soluble inorganic salts and impurities. After washing, place them in an oven to dry to constant weight, dry, crush, and pass through a 325-mesh standard sieve. Collect the fine powder that passes through the sieve. Weigh 3 g of rice husk and straw fine powder, dissolve it in 10 mL of 55% zinc chloride solution, and heat-activate it at 60 ℃ for 12 h to obtain activated rice husk and straw fine powder. 4) The exfoliated montmorillonite and activated rice husk straw powder were thoroughly mixed at a mass ratio of 3:1 and calcined at 400 °C for 1 h under an inert atmosphere to obtain a carbon-based montmorillonite composite material. 5) Add 5 mL of a 1×10⁻⁶ solution to 5 mg of carbon-based montmorillonite composite material. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0060] Comparative Example 9 1) Sodium-based montmorillonite was subjected to ion exchange to obtain sodium-based montmorillonite, which was then dried for later use. 2) Weigh 1 g of sodium montmorillonite and mix it thoroughly with 50 mL of formamide solution. React the mixture at 60 °C for 24 h under an inert atmosphere to obtain exfoliated montmorillonite. 3) Add 5 mL of 1×10⁻⁶ solution to 5 mg of exfoliated montmorillonite. 8 Bacillus subtilis at cfu / mL was stirred in a water bath at 37 °C for 6 h, centrifuged, washed multiple times to remove free bacteria, and dried to obtain a carbon-based montmorillonite composite material loaded with Bacillus subtilis, i.e. a mycotoxin detoxifier.
[0061] Table 1
[0062] Note: Calcium-based montmorillonite, exfoliated montmorillonite, and Bacillus subtilis were used as control groups in the adsorption performance study.
[0063] Table 1 shows the adsorption rates of zearalenone and vomitoxin for the samples prepared in each example and comparative example. The modified montmorillonite loaded with Bacillus subtilis prepared in Examples 1-2 has a high adsorption capacity for both zearalenone and vomitoxin, which is better than that of unloaded montmorillonite and pure Bacillus subtilis, and significantly better than that of calcium-based montmorillonite. Furthermore, the sample prepared in Example 2 has the strongest adsorption capacity for both zearalenone and vomitoxin, indicating that the preparation method provided by the present invention can effectively improve the adsorption capacity of montmorillonite for zearalenone and vomitoxin.
[0064] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All embodiments falling under the scope of the present invention... Obvious variations or modifications derived from the technical solution are still within the scope of protection of this invention.
Claims
1. A method for preparing a mycotoxin detoxifying agent, characterized in that, Includes the following steps: S1. Calcium-based montmorillonite is converted into sodium-based montmorillonite by sodium conversion, and then exfoliated montmorillonite is obtained after swelling and exfoliation treatment. S2. The crushed grain and oil processing waste is immersed in zinc chloride solution and then thermally activated to obtain activated grain and oil processing waste. S3. Mix the exfoliated montmorillonite with activated grain and oil processing waste evenly, dry it, and calcine it under an inert atmosphere to obtain a carbon-based montmorillonite composite material. S4. The obtained carbon-based montmorillonite composite material is thoroughly mixed with Bacillus subtilis bacterial solution and centrifuged to obtain carbon-based montmorillonite composite material loaded with Bacillus subtilis.
2. The preparation method according to claim 1, characterized in that, The grain and oil processing waste comes from one or more of the following: straw, peanut shells, rapeseed shells, sunflower seed shells, cottonseed shells, corn cobs, and tea seed shells. Preferably, the mass ratio of the exfoliated montmorillonite to the activated grain and oil processing waste is 1:1-20.
3. The preparation method according to claim 1, characterized in that, Bacillus subtilis is Bacillus subtilis ags617, which was deposited at the China General Microbiological Culture Collection Center on March 6, 2026, with accession number: CGMCC No. 37860; Preferably, the viable count of the Bacillus subtilis bacterial solution is 5 × 10⁻⁶. 8 -1×10 9 CFU / mL.
4. The preparation method according to claim 1, characterized in that, In step S2, the thermal activation temperature is 40-60℃ and the thermal activation time is 8-15h.
5. The preparation method according to claim 1, characterized in that, In step S3, the calcination temperature is 400-450℃ and the calcination time is 0.5-3 h.
6. The preparation method according to claim 1, characterized in that, The mass-to-volume ratio of the carbon-based montmorillonite composite material and Bacillus subtilis bacterial solution is 1 mg: 1-5 mL.
7. A mycotoxin detoxifying agent, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
8. The application of the mycotoxin detoxifier as described in claim 7 in the removal of mycotoxins.
9. The application according to claim 8, characterized in that, The application further includes: The mycotoxin detoxifier according to claim 7 is added to the mycotoxin solution and adsorbed at a constant temperature under light-protected conditions.
10. The application according to claim 9, characterized in that, The concentration of the mycotoxin solution is 1-50 mg / L; Preferably, the mycotoxin detoxifying agent has a mass concentration of 1-5 wt‰ in the mycotoxin solution; Preferably, the isothermal adsorption conditions are isothermal adsorption at 37-45℃ for 1-3 hours; Preferably, the mycotoxin solution includes one or more of vomitoxin, zearalenone, fumonisin, and aflatoxin.